Desenvolvimento de catalisadores sem platina: estudos comparativos da oxidação de metanol em 'PD''RU'/'C' e 'PT''RU'/'C' em meio alcalino - Amantéa, Bruno Estevam [UNESP] (2015)
In this work, we present a study of the activity of carbon-supported PdRu catalysts for the methanol oxidation reaction in alkaline medium, as well as the comparison with similar materials based on Pt (PtRu/C). The catalysts were synthesized by a modified poliol method with nominal atomic composition Pd:Ru and Pt: Ru of 1:1. The studies were carried out in a comparative fashion for the as-prepared materials and those thermally treated at 200 ° C and 400 ° C in an argon atmosphere. X-ray diffraction (XDR) showed incorporation of Ru into the Pd lattice, which increased with heat treatment. In contrast, Ru incorporation in Pt network was observed only after treatment at 400 °C. Transmission electronic microscopy showed average particle sizes near 3 nm for Pd and near 2 nm for Pt-based materials. Measurements of X-ray absorption spectroscopy (XAS) showed that for all materials the addition of Ru increases the vacancy of the Pd 4d band or Pt 5d band. Methanol oxidation on PdRu catalysts showed a relation with the Pd 4d band vacancy, at the time that the material with the highest vacancy was the one that showed the largest current density. The infrared spectra showed that, for both Pd and Pt materials, formate and CO32- / CO2 are the main products, while their relative amounts change with applied potential. Data indicate that methanol oxidation activity depends mainly on the electronic properties, which determine the turnover frequency. Pt catalysts showed similar behavior, with slightly higher current densities. The differences in performances, however, are not very large and, thus, substitution of Pt by Pd would be feasible.